2015
DOI: 10.1177/1591019915582942
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde leptomeningeal venous approach for dural arteriovenous fistulas at foramen magnum

Abstract: A 72-year-old man presented with sudden right homonymous hemianopsia. Work-up imaging revealed a left occipital haematoma and an arteriovenous fistula supplied by the meningeal branches to the clivus from the left vertebral artery (VA) with a rostral venous reflux into cortical veins. A microcatheter was advanced through brainstem veins into the venous collector. A compliant balloon was placed in the left VA facing the origin of feeders. The balloon was inflated to protect the vertebrobasilar circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…When TVE is performed in an ACF DAVF, after the microcatheter tip is positioned in the fistula point, arteriography of the OA and superselective venography of the microcatheter are necessary to confirm the placement of the microcatheter tip 11, 31. When performing TVE, Onyx is a good choice because it can penetrate the fistula through the cribriform plate and can pass retrogradely into the tiny transosseous arterial feeders 59. In the 48 cases we considered, we found that Onyx has become popular in EVT for ACF DAVFs since 2005.…”
Section: Discussionmentioning
confidence: 99%
“…When TVE is performed in an ACF DAVF, after the microcatheter tip is positioned in the fistula point, arteriography of the OA and superselective venography of the microcatheter are necessary to confirm the placement of the microcatheter tip 11, 31. When performing TVE, Onyx is a good choice because it can penetrate the fistula through the cribriform plate and can pass retrogradely into the tiny transosseous arterial feeders 59. In the 48 cases we considered, we found that Onyx has become popular in EVT for ACF DAVFs since 2005.…”
Section: Discussionmentioning
confidence: 99%